Serum IL-6 Level Predicts the Prognosis and Diagnosis in Cervical Cancer Patients - Cai C; Peng X; Zhang Y (International Journal of Women's Health, 2022)
Chunyan Cai, Xing Peng, Yumei Zhang Department of Gynaecology, The Affiliated Huai’an No.1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, 223300, People’s Republic of ChinaCorrespondence: Chunyan Cai, Department of Gynaecology, The Affiliated Huai’an No.1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, 223300, People’s Republic of China, Email sisicaii@126.comBackground: Interleukin-6 (IL-6) has been reported to be associated with the prognosis of cancers. As for cervical cancer (CC), previous studies investigated the association between IL-6 expression in CC tumor tissue and CC prognosis; however, no studies assessed the effects of serum IL-6 levels on the survival of CC. This study aimed to explore the effects of serum IL-6 levels on prognosis in patients with CC.Methods: In total, 327 patients with CC and 355 controls were recruited from this hospital from May 2015 to May 2016. Serum IL-6 levels were measured before treatment. The Kaplan–Meier method was utilized to estimate survival rates. The overall survival (OS) and disease-free survival (DFS) were evaluated. The univariate and multivariate Cox regression analyses were used to identify risk factors associated with the prognosis of CC.Results: We found that the serum IL-6 level in the CC group was significantly higher than that in the control group. The diagnostic value of serum IL-6 level in detecting CC patients was moderate, and the specificity and sensitivity were 77.46% and 47.09%, respectively. Data suggested that the serum IL-6 level was significantly linked with the smoking status, FIGO stage, tumor size, treatment methods, and HPV infection. The univariate and multivariate analysis indicated that FIGO stage IIB-IIIC, lymph node metastasis, and high serum IL-6 levels were negatively associated with the OS and DFS in patients with CC.Conclusion: Serum IL-6 has a moderate diagnostic ability for detecting CC and may be a potential CC biomarker. High serum IL-6 level is associated with adverse prognosis in patients with CC and could be a prognosis indicator for CC patients.Keywords: interleukin-6, cervical cancer, prognosis, diagnosis